The Play of Space : Spatial Transformation in Greek Tragedy - Rehm, Rush (Book collections on Project MUSE., 2002)
Is "space" a thing, a container, an abstraction, a metaphor, or a social construct? This much is certain: space is part and parcel of the theater, of what it is and how it works. In The Play of Space, noted classicist-director Rush Rehm offers a strikingly original approach to the spatial parameters of Greek tragedy as performed in the open-air theater of Dionysus. Emphasizing the interplay between natural place and fictional setting, between the world visible to the audience and that evoked by individual tragedies, Rehm argues for an ecology of the ancient theater, one that "nests" fifth-cent.